Study of Feeding Preference and the Effect of Some Hosts of Aphid on Some Biological Aspect of the Coccinella Septempunctata (Coleoptera: Coccinellidae) - Esraa Fadel Wathah (Journal of Global Pharma Technology, 2018)
The current study included a food preference test for C.septempunctata in a modified McDonald's way inpreferring a type of aphid than the other, as well as to know the effect of the host species of prey inattracting predators. In which the type of aphid had been studied and they are Schizaphisgraminum,Aphis Nerii and thrioaphistrifolii. The results show that adult predators are attracted towards S.graminum followed by A. nerii and T. trifolii. When the adults were exposed to plants without aphid,they showed an attraction towards the Triticumspelta, followed by Nerium oleander and Medicago sativaplants successively. The study also included the testing of aphid species at different stages of life for thementioned type. The results of the study showed that the growth rate of predator larvae differedaccording to the insect host. The longest duration of the larval stage was (16091) day when feeding on S.graminum and the shortest (12.01) day when feeding on T. trifolii. As for the pupae role, the longestduration was (5.85) day when feeding on A.nerii insect. As for adults, the duration of pre-laying eggs, thenumber of eggs, incubation and the proportion of hatching differed depending on the host insect. Thehighest pre-egg laying time was (7.95) day when feeding on Nerium oleander aphid and the least (4.77)day in feeding on T. trifolii and the highest rate of eggs lying was (800.30) and the lowest (386.00) infeeding on S. graminum. The highest egg incubation period reached (4.00) day in feeding on A. Nerii andthe lowest (2.00) day in feeding on T. trifolii. The highest percentage of egg hatch is (88.82) in feeding onS. graminum and the lowest is (60.33) % in feeding on A. neriiKeywords: Hosts, Biological aspect, Coccinella Septempunctata.